2018
DOI: 10.4103/sjg.sjg_426_17
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of and risk factors for inadequate bowel preparation in elderly patients: A prospective observational study

Abstract: Background/Aim:We conducted a prospective observational study to identify the incidence of and risk factors for inadequate bowel preparation in elderly Chinese patients.Patients and Methods:We enrolled 240 outpatients over 60 years of age scheduled for elective colonoscopy at our university hospital between November 2016 and April 2017. We recorded patient demographics, bowel preparation data, and clinical characteristics. Factors associated with inadequate bowel preparation were identified by multivariate log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
1
24
0
3
Order By: Relevance
“…This study found that patients 50 years or younger and nondiabetic patients had a statistically higher frequency of adequate bowel preparation (rated 0, 1, or 2 on Ottawa Preparation Scale overall) as rated by endoscopists. This reinforces existing literature, which lists both older age and diabetic status as risk factors for poor bowel preparation adequacy . Aging causes degeneration of the autonomic nervous system that controls enteric smooth muscles.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study found that patients 50 years or younger and nondiabetic patients had a statistically higher frequency of adequate bowel preparation (rated 0, 1, or 2 on Ottawa Preparation Scale overall) as rated by endoscopists. This reinforces existing literature, which lists both older age and diabetic status as risk factors for poor bowel preparation adequacy . Aging causes degeneration of the autonomic nervous system that controls enteric smooth muscles.…”
Section: Discussionsupporting
confidence: 85%
“…This reinforces existing literature, which lists both older age and diabetic status as risk factors for poor bowel preparation adequacy. [10][11][12] Aging causes degeneration of the autonomic nervous system that controls enteric smooth muscles. Furthermore, older patients tend to be more immobile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…looked at incidence and risk factors for inadequate bowel preparation among elderly patients. [ 8 ] In this prospective trial, the rate of inadequate bowel preparation among ambulatory patients above the age of 60 was 34.6%. In a unique aspect of the study, subjects were required to walk at least 30 min while taking the laxative.…”
mentioning
confidence: 87%
“…Insufficient cleansing or preparation is associated with a low diagnostic yield, a higher rate of canceled procedures, corresponding increased costs, lengthy procedures, and a higher risk of complications. The existing literature has identified multiple factors contributing to suboptimal bowel preparation, including comorbidities, age, gender, use of antidepressants, education level, history of abdominal surgery, non-compliance with preparation instructions, and the timing of bowel preparation before the colonoscopy (2,3). Recent studies suggest that the time interval between the last intake of bowel preparation medication and the start of colonoscopy, is a significant factor in determining the efficacy of cleansing (4).…”
Section: ' Introductionmentioning
confidence: 99%